Primary Age-Related Tauopathy in Human Subcortical Nuclei - Zhu, Keqing; Wang, Xin; Sun, Bing; Wu, Juanli; Lu, Hui; Zhang, Xiaoling; Liang, Huazheng; Zhang, Dandan; Liu, Chong (Frontiers in Neuroscience, 2019)
The present study aimed to determine the spatial distribution patterns of hyperphosphorylated tau-immunoreactive cells in subcortical nuclei of post-mortem human brain with primary age-related tauopathy (PART). The subcortical tauopathy has important pathological and clinical implications. Expression of tau was examined in different subcortical regions of definite PART cases with a Braak neurofibrillary tangle stage >0 and ≤IV, and with a Thal phase 0 (no beta-amyloid present). Post-mortem brain tissue of PART was studied using immunohistochemistry and subsequent semi-quantitative assessment with Braak NFT stage -matched pre-Alzheimer's disease (AD) and AD cases as a control. Expression of tau was frequently found in subcortical nuclei including the substantia nigra, inferior colliculus, locus coeruleus, medulla oblongata in the brainstem, the caudate, putamen, nucleus globus pallidus in the striatum, the hypothalamus, thalamus, subthalamus in the diencephalon, and the cervical spinal cord in both PART and AD, but not in the dentate nucleus of the cerebellum. A positive correlation was found between the Braak NFT stage and the tau distribution (qualitative) /tau density (quantitative) in PART and AD. Brainstem nuclei were commonly involved in early PART with NFT Braak stage I/II, there was no preference among the substantia nigra, inferior colliculus, locus caeruleus and medulla oblongata. The prevalence and severity of tau pathology in subcortical nuclei of PART and AD were positively correlated with NFT Braak stage, suggesting that these nuclei were increasingly involved as PART and AD progressed. Subcortical nuclei were probably the sites initially affected by aging associated tau pathology, especially the brainstem nuclei including the substantia nigra, inferior colliculus, locus caeruleus and medulla oblongata.